Bielinis, L., 2011. The President as a “Political Cliché,” or the Polemical Marginalia of a Philologist - Čičinskaitė, Regina (Respectus Philologicus, 2012)
Bielinis, Lauras, 2011. Prezidentė. Kaunas: Knygius; Kitos knygos. 165 p. ISBN 978-427-046-8
Keywords: none